Prolonged reserves accumulation, credit booms, asset prices and monetary policy in Asia - Andrew J. Filardo; Pierre L. Siklos (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This paper examines past evidence of prolonged periods of reserve accumulation in Asian emerging market economies and the direct and indirect implications for monetary stability through the potential impact of such episodes on financial stability. The empirical research focuses on identifying periods of prolonged interventions and correlations with key macro-financial aggregates. Related changes in central bank balance sheets are also examined, especially in periods when the interventions are linked to strong capital inflows. In particular, we consider whether changes in the central bank's balance sheet from prolonged intervention lead to spillovers to the balance sheet of the private sector. We explore the possible forms of the spillovers and the consequences on asset prices (e.g., housing prices, equity prices, the growth in domestic credit). Policy implications are drawn. Finally, we propose a new indicator of reserves adequacy and excessive foreign exchange reserves accumulation based on a factor model. Two broad conclusions emerge from the stylized facts and the econometric evidence. First, the best protection against costly reserves accumulation is a more flexible exchange rate. Second, the necessity to accumulate reserves as a bulwark against goods price inflation is misplaced. Instead, there is a strong link between asset price movements and the likelihood of accumulating foreign exchange reserves that are costly.
URN:NBN:fi:bof-201408072158
Keywords: F41; F32; E44; D52; 330; foreign exchange reserves accumulation; monetary and financial stability